2015
DOI: 10.1097/aln.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maturation and Aging and Pulmonary Responses in Animal Models of Lung Injury

Abstract: Increasing age seems to be correlated with exaggerated pulmonary responses to injury, ultimately leading to more severe lung injury. Pulmonary inflammation seems relatively suppressed in infants/juveniles, whereas in the middle aged/elderly, the inflammatory response seems delayed but aggravated. This implies that investigators and clinicians need to use caution about extrapolating results from adolescent or youngadult animals to pediatric or elderly patients in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 95 publications
0
32
0
1
Order By: Relevance
“…Besides, most experiments use young male rodents that almost never have comorbidities for the evaluation of new treatments for ARDS, while patient populations seen in intensive care units are elderly and frequently have concomitant diseases such as diabetes mellitus, chronic obstructive pulmonary disease or active cancer [54]. The few studies that compared elderly rodents to younger ones indeed found a difference in the biological response between these groups [55,56].…”
Section: Ineffective Interventionsmentioning
confidence: 99%
“…Besides, most experiments use young male rodents that almost never have comorbidities for the evaluation of new treatments for ARDS, while patient populations seen in intensive care units are elderly and frequently have concomitant diseases such as diabetes mellitus, chronic obstructive pulmonary disease or active cancer [54]. The few studies that compared elderly rodents to younger ones indeed found a difference in the biological response between these groups [55,56].…”
Section: Ineffective Interventionsmentioning
confidence: 99%
“…У детей важно проводить тщательный интраоперационный мониторинг с контролем глюкозы крови в течение оперативного вмешательства [17,18], чтобы обеспечить нормогликемию.…”
Section: результаты и обсуждениеunclassified
“…Mortality rates and hospital discharge to extended care facilities increased consistently for each decade of age over the age of 65 years in mechanically ventilated patients (22). Epidemiological studies also suggest that age is a predictive factor in the severity of VILI; however, the exact molecular mechanisms between age and VILI are still unknown (16, 55, 63). In rodent models of VILI, we and others have shown that age increases susceptibility to ventilator-induced edema, injury, and mortality (1, 36).…”
Section: Introductionmentioning
confidence: 99%